Financial Development, Financial Structure, and Domestic Investment: International Evidence - Léonce Ndikumana (University of Massachusetts, Department of Economics, 2003)
Does it matter for domestic investment whether a country's financial system is bank based or stock-market based? This paper posits that financial intermediation affects domestic investment notably by alleviating financing constraints, allowing firms to increase investment in response to increased demand for output. The key result is that the structure of the financial system has no independent effect on investment, in the sense that it does not enhance the response of investment to changes in output, while financial development makes investment more responsive to output growth. Consequently, rather than promoting a particular type of financial structure, countries should implement policies that reduce transactions costs in financial intermediation and enforce creditor and investor rights. This will facilitate the development of banks and stock markets, which will stimulate domestic investment.
Keywords: 330; domestic investment; financial development; financial structure; bank-based systems; stock-market-based systems